CUSTOMER RELATIONSHIP MANAGEMENT AS A STRATEGIC CAPABILITY FOR ICT ENTREPRENEURSHIP IN THE DIGITAL ECONOMY - Rita Ambarwati (Journal of Artificial Intelligence and Digital Economy, 2026)
Objective: This study examines the implementation of CRM in an ICT service company and explores its contribution to customer satisfaction, customer retention, and long-term relationship development. Method: Employing a qualitative descriptive design, the study adopts Robert K. Yin’s case study approach to investigate CRM as an integrated managerial and entrepreneurial process. The analysis examines the implementation of CRM through four interconnected strategic stages: customer portfolio analysis, customer value creation, business network alignment, and customer life-cycle management. Results: The findings demonstrate that CRM strengthens the firm’s capacity to identify customer behavior, personalize digital services, respond effectively to changing customer expectations, and cultivate customer loyalty. Moreover, an integrated CRM strategy enables ICT service firms to combine customer information, service quality, digital interaction, and relationship-building practices to support competitive differentiation and business sustainability. Novelty: The originality of this study lies in conceptualizing CRM not merely as an information technology application, but as a dynamic strategic capability that connects customer intelligence, digital value creation, entrepreneurial responsiveness, and long-term relationship management. The study provides practical implications for ICT entrepreneurs and service firms seeking to enhance customer experience, retain profitable customers, expand their customer base, and achieve sustainable growth within an increasingly competitive digital economy.